2019
DOI: 10.3897/zookeys.888.37982
|View full text |Cite
|
Sign up to set email alerts
|

Who are you, Griselda? A replacement name for a new genus of the Asiatic short-tailed shrews (Mammalia, Eulipotyphla, Soricidae): molecular and morphological analyses with the discussion of tribal affinities

Abstract: The first genetic study of the holotype of the Gansu short-tailed shrew, Blarinella griselda Thomas, 1912, is presented. The mitochondrial analysis demonstrated that the type specimen of B. griselda is close to several recently collected specimens from southern Gansu, northern Sichuan and Shaanxi, which are highly distinct from the two species of Asiatic short-tailed shrews of southern Sichuan, Yunnan, and Vietnam, B. quadraticauda and B. wardi. Our analysis of four nuclear genes supported the placement of B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Previously, we successfully obtained DNA sequences for historical reptile samples: Phrynocephalus rossicowi (Reptilia), Dipus saggita (Mammalia), Blarinella griselda (Mammalia), Tonkinodentus lestes (Chilopoda), etc. [ 23 , 24 , 25 , 26 ]. This paper attempts to use the possibilities of studying historical DNA for the clarification of unsolved problems in this taxonomically challenging complex.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we successfully obtained DNA sequences for historical reptile samples: Phrynocephalus rossicowi (Reptilia), Dipus saggita (Mammalia), Blarinella griselda (Mammalia), Tonkinodentus lestes (Chilopoda), etc. [ 23 , 24 , 25 , 26 ]. This paper attempts to use the possibilities of studying historical DNA for the clarification of unsolved problems in this taxonomically challenging complex.…”
Section: Introductionmentioning
confidence: 99%
“…To a large extent, this is associated with their new role as a source of archive DNA for evolutionary and taxonomic research ( Payne & Sorenson, 2002 ; Irestedt et al, 2006 ; Rowe et al, 2011 ; Bi et al, 2013 ). In particular, genetic data obtained from museum specimens are often indispensable for studies of rare, protected, or poorly accessible species ( Ruane & Austin, 2017 ; Bannikova et al, 2019 ; Tsai et al, 2019 ; Turvey et al, 2019 ). Within the latter category, several groups of mammals are endemic to mountain regions of Central Asia (Tibet, the Himalayas, Tianshan, Altai), including several insufficiently studied species of birch mice ( Sicista Griffith, 1827; Sminthidae; Rodentia).…”
Section: Introductionmentioning
confidence: 99%
“…These animals are mainly distributed in central and southwestern China and adjacent areas (Burgin and He 2018). The Asiatic short-tailed shrews currently comprise the two genera Blarinella Thomas, 1911 (suggested common name: West Asian short-tailed shrews) and Parablarinella Bannikova et al, 2019 (suggested common name: East Asian short-tailed shrews)—and three species: B. quadraticauda (Milne Edwards, 1872); B. wardi Thomas, 1915; and P. griselda (Thomas, 1912). A well-resolved taxonomic account of the Asiatic short-tailed shrews is important for biomedical applications and human safety, as a recent study showed that B. quadraticauda has oral venom systems, with the venom capable of inducing blood hypercoagulation and hypertension (Liao et al 2022).…”
mentioning
confidence: 99%
“…Bannikova et al (2019) pointed out that the new genus name previously was assigned to a subgenus of African beetles (genus Agrilus ) and proposed a new genus name, Parablarinella . Currently, P. griselda is only recorded in southern Gansu, north Sichuan, southern Shaanxi, and southern Ningxia (Bannikova et al 2019; Pu et al 2020); B. wardi is distributed in northern Myanmar and western Yunnan, China; and B. quadraticauda is widespread in central and southwestern China (Chongqing, Hubei, Sichuan, Shaanxi, Yunnan, Chongqing, Hubei, and Sichuan Provinces) and adjacent North Vietnam. Thus, Western Hubei Province (Changyang County) is currently considered the easternmost distribution of the Asiatic short-tailed shrews (Burgin and He 2018; Bannikova et al 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation